(untitled) (Bangladesh Medical Journal, 2012)
Respiratory tract infections (RTIs) are a major health problem in developing countries. RTIs are the most common reason for physician visits and prescription of antibiotics. Cefixime is quickly establishing as a potent broad-spectrum antibiotic with a variety of indications. This observational study was designed to describe the treatment pattern of third generation oral cefixime in managing RTIs in general practice. This noncontrolled, multicenter, observational registry was carried out from March 2009 to July 2010. During this period 2400 patients aged 3 years to 76 years suffering from RTIs were enrolled by general physicians throughout the country. Study variable were socio demographic, signs and symptoms, clinical diagnosis, investigations, antimicrobial prescribed and clinical outcome. Clinical outcome was determined based on improvement of signs and symptoms. Compliance, efficacy and tolerance were assessed on days 7 and 10. The enrolled patients were considered for analysis. The mean age was 26.59 (± 18.10) years and 62% of patients were male. Common presenting signs and symptoms were fever, cough, shortness of breath and increased sputum volume in 80%, 75%, 39%, and 12% respectively. From prescriptions, pneumonia, acute bronchitis, acute exacerbation of chronic bronchitis and lung abscess were the diagnosis in 42%, 26%, 24% and 3% of the prescriptions, respectively. Following the treatment with cefixime clinically cured, much improved and better were obtained in 77%, 21% and 2% respectively. Furthermore, the rate of adverse events were insignificant. The study showed clinical symptoms improved rapidly and high rates of clinical cure were achieved. More over, the rate of adverse events were relatively quite low. The results supports the use of cefixime for a variety of respiratory infections in adult and pediatric patients in Bangladesh. DOI: http://dx.doi.org/10.3329/bmj.v40i1.9962 BMJ 2011; 40(1): 39-42